2016
DOI: 10.1371/journal.pone.0149516
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Copper Uptake from Blood Plasma Ceruloplasmin by Mammalian Cells

Abstract: Ceruloplasmin, the main copper binding protein in blood plasma, has been of particular interest for its role in efflux of iron from cells, but has additional functions. Here we tested the hypothesis that it releases its copper for cell uptake by interacting with a cell surface reductase and transporters, producing apoceruloplasmin. Uptake and transepithelial transport of copper from ceruloplasmin was demonstrated with mammary epithelial cell monolayers (PMC42) with tight junctions grown in bicameral chambers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 70 publications
4
98
0
Order By: Relevance
“…Everolimus treatment improved autism symptoms in all four cases with increased serum Cp and Tf levels. As described above, mTOR activity regulates iron and copper homeostasis through modulating Tf as an iron mediator [6] and Cp as a copper mediator [7]. Thus, the present findings suggest that everolimus-induced attenuation of mTOR hyperactivity results in increased serum Tf and Cp levels to induce the homeostatic balance between mTOR activity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Everolimus treatment improved autism symptoms in all four cases with increased serum Cp and Tf levels. As described above, mTOR activity regulates iron and copper homeostasis through modulating Tf as an iron mediator [6] and Cp as a copper mediator [7]. Thus, the present findings suggest that everolimus-induced attenuation of mTOR hyperactivity results in increased serum Tf and Cp levels to induce the homeostatic balance between mTOR activity.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, increased intracellular copper levels suppress mTOR signaling [5]. Thus, mTOR activity may regulate iron and copper homeostasis with Tf acting as an iron mediator [6] and ceruloplasmin (Cp) as a copper mediator [7]. Oxidized low-density lipoprotein (oxLDL) suppresses the P13K/AKT/mTOR signaling pathway as the oxidative stress marker [8].…”
Section: Introductionmentioning
confidence: 99%
“…Drawing these strands together, pharmacological effects of everolimus may be related to increases in serum levels of antioxidants. Cp is an important serum antioxidant [42] and the main copper binding protein in blood plasma [43]. Previous studies have reported that increased intracellular copper levels suppressed mTOR signaling [44], and that copper treatment down regulated mTOR signaling [45].…”
Section: Discussionmentioning
confidence: 99%
“…2. Starting with ionic copper(II) in blood, either from direct injection of ionic copper compounds or through dismantling of copper(II) complexes, copper(II) is quickly reduced to Cu(I) by reductases [102][103][104][105], immediately binding to copper-binding proteins. On the other hand, tumor hypoxia stimulates CTR-1 expression [29,94], which then binds to Cu(I) and is transported into the tumor cells.…”
Section: Reconsidering the Copper Pathways Under Tumor Hypoxiamentioning
confidence: 99%